2015
DOI: 10.1097/gme.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory comparison of vaginal glycogen and Lactobacillus levels in premenopausal and postmenopausal women

Abstract: Objective Previous studies have suggested that glycogen expression in vaginal epithelium decreases at menopause, resulting in reduced levels of lactobacilli. However, free glycogen in genital fluids and its relationship to Lactobacillus levels has not been compared in pre- and post-menopausal women. Methods 82 cervico-vaginal lavage samples were collected at different phases of the menstrual cycle from 11 pre-menopausal (4 HIV-uninfected and 7 HIV-infected) and 12 post-menopausal (7 HIV-uninfected and 5 HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 29 publications
5
58
2
Order By: Relevance
“…Mirmonsef et al showed a correlation between quantity of vaginal lactobacilli and free vaginal glycogen, but did not see a link between serum estrogen and either vaginal glycogen or Lactobacillus levels. 7 In Chinese women with and without vaginal signs and symptoms of atrophy, while serum estradiol levels were similar, relative proportion of vaginal lactobacilli was not. 6 These data, and our findings, suggest that there may not be direct links between serum estrogen, glycogen and Lactobacillus colonization as previously postulated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mirmonsef et al showed a correlation between quantity of vaginal lactobacilli and free vaginal glycogen, but did not see a link between serum estrogen and either vaginal glycogen or Lactobacillus levels. 7 In Chinese women with and without vaginal signs and symptoms of atrophy, while serum estradiol levels were similar, relative proportion of vaginal lactobacilli was not. 6 These data, and our findings, suggest that there may not be direct links between serum estrogen, glycogen and Lactobacillus colonization as previously postulated.…”
Section: Discussionmentioning
confidence: 96%
“…3,4,6 Recent data have shown that free glycogen in vaginal fluid, which is liberated from epithelial cells by enzymes like α-amylase, is associated with Lactobacillus colonization in both pre- and postmenopausal women, suggesting glycogen may be a mediating factor for Lactobacillus presence. 7,8 In premenopausal women, serum estrogen levels were not correlated with free vaginal glycogen levels, but this relationship has not been examined in postmenopausal women. 9 …”
Section: Introductionmentioning
confidence: 99%
“…These changes were suggested to be dependent on estrogen levels, because the low pH and Lactobacillus spp. colonization in the vagina occur at the same time as when estrogen levels are increasing [94]. Gorodeski et al suggested that estrogen contributes to the acidification of the vaginal pH by upregulation of proton secretion via the apical membrane of vaginal ectocervical cells in their epithelial cell line model [95].…”
Section: Hormonesmentioning
confidence: 98%
“…The amount and composition of cervical mucus, as well as the amount of glycogen available, vary among women and through time in a single woman. Temporal variation in these characteristics occurs both on the scale of the menstrual cycle as well as through the lifetime of an individual (15)(16)(17)(18)(19). Additionally, the host can effect change in the vaginal communities via the immune system.…”
mentioning
confidence: 99%